Concentration of BOD5 in the Lacustrine and Transition Zones Koto Panjang Reservoir, Kampar District, Riau Province. - Silaen, William Fransisco; Siagian, Madju; Simarmata, Asmika H (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
In the Koto Panjang Reservoir, the floating net caged fish culture produced organic meterials that negatively affects the water quality. A study aims to understand the concentration of BOD5 in the lacustrine and transition zones has been conducted from March to April 2016. There were 4 sampling sites, in the lacustrine 1 (L1), lacustrine 2 (L2), transition 1 (T1) and transition (T2). The vertical sampling points were decided based on transparency of the waters (at the surface, 3m, 6m, 12m, and in the bottom). The number of vertical sampling sites was depended on the depth of the water. 2 Secchi depth, 4 Secchi depth, 6 Secchi depth and in the bottom of the water. Water quality parameters measured were dissolved oxygen, free carbondioxide, nitrate, pH, phospate, temperature, and transparency. Results shown that BOD5 concentration in the lakustrine zone was 2.92 – 9.34 mg/L and in transition zone was 2.13 – 7.81 mg/L. Two way anova analysis shown that there was no difference in BOD5 concentration between zones. The floating net cage activity influences the BOD5 concentration in the Koto Panjang Reservoir.Keywords: Koto Panjang reservoir, BOD, lacustrine, transition